Kontrol Diri dan Intensitas Penggunaan Gawai sebagai Prediktor Perilaku Prososial Remaja - Siti Nur Rohima; Yudi Krisno Wicaksono (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study is based on the phenomenon of increasing gadget use among adolescents, which is suspected to impact the quality of social interactions and the development of prosocial behavior in the school environment. The purpose of this study is to examine the role of self-control and the level of gadget use as predictors of prosocial behavior in adolescents. The study used a quantitative approach with a causal associative design. The study population consisted of 380 students, with a sample of 80 students determined through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results showed that self-control had a negative and significant effect on prosocial behavior, while the intensity of gadget use had a positive and significant effect. Together, these two variables had a significant influence, contributing 63.4% to the variation in prosocial behavior. These findings indicate that adolescent prosocial behavior is influenced not only by internal factors such as self-control, but also by patterns of digital technology use. Therefore, efforts to strengthen self-control and manage gadget use appropriately are needed to support the development of adolescent prosocial behavior in the digital era.